Critical Discourse Analysis on Contemporary Indonesian Poetry from 1966-1998 - Wiguna, Riefki Fajar Ganda; Kombong, Maxymilianus Soter Mite (Indonesian Journal of English Language Studies (IJELS), 2016)
The  growth  of  Indonesian  literary works  began  since  the  generation  of  Pujangga  Baru brought literature to the surface. Many poets, novelists, and writers emerged, bringing about their works which remain popular in the present. This paper is a critical discourse analysis which aims to find the dominant ideology represented in the Contemporary Indonesian Poetry from the 1960s to the 1970s. The data were taken from Contemporary Indonesian Poetry translated by Harry Aveling (1975). There are 11 poems that were analyzed in this study. They are Sermon, Pickpocket’s Advice to His Mistress, and Prostitutes of Jakarta Unite! by W.S  Rendra,  Two  Poems  with  One  Title,  Space,  and  Who  Are  You  by  Sapardi  Djoko Damono, Between Us, Prayer and Image by Ajip Rosidi, and A Tale Before Sleep and Cold Unregistered by Gunawan Muhammad. By using the Seven Building Tasks proposed by James Paul Gee (2011), the researchers analyzed each poem based on the seven tasks. The result shows that the dominant ideologies in Contemporary Indonesian Poetry from the 1960s to  the  1970s  are  in  the matters  of socialism  and  humanism.  Socialism  here  covers  the condition of social life at that time where there power abuse occurred from the powerful people  towards  the  powerless  ones.  On  the  other  hand,  humanism  merely  covers  the condition of human beings, especially Indonesians, at that time. Keywords:  ideology,  critical  discourse  analysis,  seven  building  tasks,  contemporaryIndonesian poetry.